(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of this study was to determine the effect of teacher competence, infrastructure, and work discipline on student achievement at SDN 1 and Iwul Cluster 2 Iwul. This research method uses descriptive and verification analysis with a quantitative approach. The source of this research uses primary data. This research data collection using a questionnaire. The sample of this research was 87 students of SDN 1 and Iwul Gugus 2 Iwul class V and class VI using the saturated sampling technique. Data analysis was done by descriptive analysis and multiple regression analysis. The results of this study indicate that there is a positive and significantinfluence between Teacher Competence, Infrastructure, and Work Discipline simultaneously on Student Learning Achievement, where these variables have an influence of 83.7% on Student Achievement. Partially there is a positive and significant influence between Teacher Competence, Infrastructure, and Work Discipline on Student Learning Achievement. The influence of teacher competence on student achievement is 34.13%, the influence of facilities and infrastructure on student achievement is 27.84% and the influence of work discipline on student achievement is 21.67%.